Plant Growth Promoting Endophytic Bacteria of Coffea canephora and Coffea arabica L. in UB Forest - Pratiwi, Esti Rizkiana; Ardyati, Tri; Suharjono, Suharjono (The Journal of Experimental Life Science, 2020)
Plant Growth Promoting (PGP) Endophytic bacteria are used as an alternative biofertilizer to support soil health and plant productivity. This research aimed to isolate, analyze the potential, and identify the endophytic bacteria of Robusta and Arabica coffee plants as biofertilizer agents. Endophytic bacteria were isolated from the roots of coffee plants and tested for their potential to produce IAA, phosphate-solubilizing, and nitrogen fixation. Potential endophytic bacterial isolates were identified based on 16S rDNA sequence similarity. Total isolates from Robusta coffee consisting of ten IAA-producing bacteria, eight phosphate-solubilizing, and seven nitrogen fixation bacteria isolates. Total isolates from Arabica coffee roots were 12 isolates of IAA-producing bacteria, seven isolates of phosphate-solubilizing bacteria, and six isolates of nitrogen fixation bacteria. The highest potential of the isolate from Robusta roots was SS.E2 isolate to produce IAA 110.73 μg.mL-1; SS.P3 isolate to dissolve phosphate 4.42 μg.mL-1, and SS.N2 isolate to produce ammonium 3.15 μg.mL-1. The highest potential of the isolate from Arabica roots was SW.E9 isolate to produce IAA up to 257.16 μg.mL-1; SW.P5 isolate to dissolve phosphate up to 4.55 μg.mL-1; and SW.N6 isolate to produce ammonium up to 1.16 μg.mL-1. Isolates SS.E2, SW.E9, SS.P3, SW.P5, SS.N2, and SW.N6 were respectively identified as Bacillus cereus ATCC 14579, Bacillus cereus ATCC 14579, Rahnella aquatilis B35, Kluyvera intermedia TPY16, Rahnella aquatilis B35, and Pseudomonas tolaasii NCPPB 2192. Potential PGP isolates can be developed as biofertilizer agents for the coffee plant. Keywords: Coffee, Endophytic bacteria, IAA, Nitrogen, Phosphate